Cases on teaching English for academic purposes (EAP) during Covid-19 insights from around the world - Kohnke, Lucas (Information Science Reference, 2023)
"This book explores the effect of emergency remote teaching in offering quality English for Academic Purposes (EAP) provision to second/foreign-language students and preparing them for their university studies in response to COVID-19 from a variety of contexts around the world"--